2008
DOI: 10.22621/cfn.v122i3.606
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Use by the Eastern Sand Darter, <em>Ammocrypta pellucida</em>, in Two Lake Champlain Tributaries

Abstract: O'Brien, Shannon M., and Douglas E. Facey. 2008. Habitat use by the Eastern Sand Darter, Ammocrypta pellucida, in two Lake Champlain tributaries. Canadian Field-Naturalist 122(3): 239-246.The Eastern Sand Darter (Ammocrypta pellucida) is endangered or threatened throughout much of its range, which includes the St. Lawrence-Lake Ontario drainage of southern Ontario and Quebec and several Vermont tributaries of Lake Champlain. The species is known for its tendency to burrow, and field observations have suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…In general, western sand darters selected for a narrower range of substrate sizes compared to the eastern sand darter, and habitat use overlap occurred most often in the medium sand category. This study was contingent upon five designated substrate types that were similar to previous sand darter habitat use studies (Daniels 1993;O'Brien & Facey 2008) and represented a range of benthic habitats both species may encounter (Welsh & Perry 1998;Facey & O'Brien 2004;Tessler et al 2012). Habitat use in the field could vary compared to the aquaria-based study, but our results demonstrated that each sand darter species exhibited nonrandom selection of substrate types, indicating that a certain benthic habitat was preferred compared to the other available sizes.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…In general, western sand darters selected for a narrower range of substrate sizes compared to the eastern sand darter, and habitat use overlap occurred most often in the medium sand category. This study was contingent upon five designated substrate types that were similar to previous sand darter habitat use studies (Daniels 1993;O'Brien & Facey 2008) and represented a range of benthic habitats both species may encounter (Welsh & Perry 1998;Facey & O'Brien 2004;Tessler et al 2012). Habitat use in the field could vary compared to the aquaria-based study, but our results demonstrated that each sand darter species exhibited nonrandom selection of substrate types, indicating that a certain benthic habitat was preferred compared to the other available sizes.…”
Section: Discussionmentioning
confidence: 52%
“…The western and eastern sand darters mean total length was 52.7 mm (SD 2.30 mm) and 56.9 mm (3.24 mm), respectively. For collection, a straight 1.5 £ 3 m seine with 3 mm mesh was used in wadable areas of the river, including upstream and downstream parallel seine hauls and perpendicular hauls pulled into shore (O'Brien & Facey 2008;Driver & Adams 2013). Sampling for the sand darters occurred during the fall because the Elk River experiences lower flows (i.e.…”
Section: Fish Collection and Aquaria Setupmentioning
confidence: 99%
See 3 more Smart Citations